Teachers' Beliefs About Rigor of Curriculum for English Language Learners. Issue 1 (2nd January 2019) - Murphy, Audrey Figueroa; Torff, Bruce
Abstract: Survey research tested the hypothesis that teachers support less rigorous curriculum for English language learners (ELLs) than for general-education (GE) students. Participating teachers worked in urban schools with large populations of ELLs. Teachers rated descriptions of instructional activities that differed in demand for critical thinking (CT), a proxy for rigor of curriculum. Teachers favored less rigorous curriculum for ELL students, especially concerning high-CT activities. Such beliefs likely contribute to achievement gaps between ELLs and GE students.